Striving for Adopting and Adapting Information Technology: A Qualitative Study of Informal Skills Learners in Nepal - Baral, Durga Prasad (Journal of Training and Development, 2026)
In this study, I explore how informal skills learners adopt (learn and use new digital tools) and adapt (modify their traditional learning practices to fit) these technologies in their everyday work setting. Drawing on a qualitative case study with fieldwork from pottery, metalcrafts, fast-food services, and motorcycle mechanics occupational sectors, we have used an interpretive approach guided by workplace learning theory with technological determinism insights. I have collected the data through kurakani (informal interviews) and observations with eight research participants, focusing on their experiences of using local (basic, manual) as well as information technologies. The findings reveal that although there is limited access to advanced tools and formal training, informal skills learners exhibit solid adaptability and initiative. With the technologies available, they learn new skills through different approaches, such as observation, imitation, and digital platforms like YouTube. It is explored that informal skills learners often rely on informal networks and self-directed learning to cope with technological transformations. The study concludes that there is an acute need for targeted support from the state and public institutions, including awareness programs and flexible training.